Safety regulatory framework for hydrogen fusion reactors in China. (23rd August 2019) - Shen, Xinyuan; Chen, Zhibin; Wang, Zhen; Wang, Haixia; Chen, Shanqi; Ge, Daochuan; Chen, Chao; Jiang, Jieqiong; Hu, Liqin; Yu, Jie; Wu, Yican
Abstract: China is very ambitious for the development of fusion energy system using the fusion reaction of hydrogen isotopes. According to China magnetic confinement fusion development roadmap, the China Fusion Engineering Test Reactor (CFETR) is expected to be constructed in 2020s, which will be the first hydrogen fusion reactor in China. However, China has not yet established the safety regulatory framework for the licensing of a hydrogen fusion reactor such as CFETR, while the existing regulatory framework is based on the fission reactor development and there are huge differences in the safety characteristics between fusion reactor and fission reactor. In this paper, China's nuclear safety regulation system is reviewed and then key issues are raised for adapting the regulatory framework to the hydrogen fusion reactor, considering the fusion safety characteristics as well as lessons learnt from the licensing of ITER in the French regulations. Gaps between China nuclear safety regulations and CFETR safety concerned demands are also identified and discussed. It is suggested that the engineering design of CFETR shall be done together with the development of corresponding safety regulatory framework. Highlights: Gaps identified between China nuclear safety regulations and CFETR safety concerned demands. Key issues raised for the adaption of regulatory framework to hydrogen fusion reactor. Overview of China's existing nuclear safety regulation system.